1975
DOI: 10.4269/ajtmh.1975.24.439
|View full text |Cite
|
Sign up to set email alerts
|

Soil Survival of Toxoplasma Oocysts in Kansas and Costa Rica

Abstract: Toxoplasma oocysts in cat feces were marked with a tracer amount of strontium-85 (85-SR), and were superficially buried simulating the natural disposal of feces by cats. Oocyst infectivity in Costa Rica was followed qualitatively and persisted for 1 year in three shaded sites, two moist, and one relatively dry site. Oocyst infectivity was quantitated in the Kansas deposit over a period of 18 months, including two winters. After initial mixing in soil, the level of infectivity remained fairly stable. Infectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
140
0
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(147 citation statements)
references
References 0 publications
2
140
0
5
Order By: Relevance
“…In the short term, it has been suggested that cats are pivotal to the transmission of T. gondii as they shed millions of oocysts into the environment, providing a large, persistent reservoir of infection for intermediate hosts [19]. However, there are other opportunities for transmission to intermediate hosts, and production of oocysts in a cat may not necessarily result in the greatest dissemination of the parasite.…”
Section: Is the Sexual Cycle Important Enough For The Evolution Of Admentioning
confidence: 99%
“…In the short term, it has been suggested that cats are pivotal to the transmission of T. gondii as they shed millions of oocysts into the environment, providing a large, persistent reservoir of infection for intermediate hosts [19]. However, there are other opportunities for transmission to intermediate hosts, and production of oocysts in a cat may not necessarily result in the greatest dissemination of the parasite.…”
Section: Is the Sexual Cycle Important Enough For The Evolution Of Admentioning
confidence: 99%
“…Oocyst survival is maximal (> 200 days) for temperatures comprised between -6°C and +20 °C [79]. Above +20°C, dessication of oocysts may occur [41,80,81], but moisture should prevent it [82,83]. Under-6°C, the survival of oocysts is reduced and their capacity to sporulate is lost [79], although one may hypothesize that snow cover may protect them from cold.…”
Section: Temporal Dynamicsmentioning
confidence: 99%
“…Frenkel et al (1975) demonstrated that sporulated T. gondii oocysts in soil could survive for 18 mo. Drinking unfiltered water is a risk factor for obtaining T. gondii infections (Bahia-Oliveira et al, 2003), and outbreaks of waterborne infections have been reported (see Dubey, 2004).…”
mentioning
confidence: 99%